Short changed? The market's reaction to the short sale ban of 2008 - Louis Gagnon; Jonathan Witmer (Bank of Canada, 2009)
Do short sales restrictions have an impact on security prices? We address this question in the context of a natural experiment surrounding the short sale ban of 2008 using a comprehensive sample of Canadian stocks cross-listed in the U.S. Among financial stocks, which were singled out by the ban in both countries, we observe a significant increase (74 bps) in the difference between the U.S. share price and the Canadian share price. We also observe an impressive and surprising migration of the trading volume from the U.S. to Canada among financial stocks during the ban. Both price and volume effects are reversed after the ban and neither effect manifests itself among the nonfinancial stocks. Our findings support the view that prices reflect a more optimistic valuation when pessimistic investors are kept out of the market by binding short-sales restrictions (Miller (1977)). Our findings also imply that pessimistic investors were more preponderant in the U.S. than in Canada, which is corroborated by the fact that the short interest ratio for our sample stocks was much larger in the U.S. than in Canada prior to the ban.
Keywords: F30; G01; G18; G20; 330; Financial markets; International topics; Finanzmarkt; Wertpapierhandel; Leerverkauf; Regulierung; Kapitalmobilität; Zinsdifferenz; USA; Kanada